Analysis of Skin Humidity Variation Between Sasang Types. (2009) - Jung, Soon-Oh; Park, Soo-Jin; Chae, Han; Park, Soo Hyun; Hwang, Minwoo; Kim, Sang-Hyuk; Kwon, Young-Kyu
Abstract : The purpose of this study was to examine the relationship between variations in skin humidity (SH) induced by perspiration across Sasang types and to identify novel and effective Sasang classification factors. We also analyzed the responses of each Sasang type to sweating-related QSCC II items. The results revealed a significant difference in SH across gender and significant differences in SH before and after perspiration between Tae-Eum and So-Eum men. In addition, Tae-Eum women showed significant differences in SH compared with women classified as another Sasang type. Furthermore, evaluation of the items related to sweating in the QSCC II and their relationship to each constitution revealed a significant difference between Tae-Eum and other Sasang types. Overall, the results of this study indicate that there is a distinct SH difference following perspiration between Tae-Eum and other Sasang types. Such findings may aid in Sasang typology diagnostic testing with the support of further sophisticated clinical studies.